An investigation on machinability of nodular cast iron by WEDM - Özdemir, N; Özek, C (Springer London Ltd, 2006)
In this study, the machinability of standard GGG40 nodular cast iron by WEDM using different parameters (machining voltage, current, wire speed, and pulse duration) was investigated. From the results, the increase in surface roughness and cutting rate clearly follows the trend indicated with increasing discharge energy as a result of an increase of current and pulse-on time, because the increased discharge energy will produce larger and deeper discharge craters. Three zones were identified in rough regimes of machining for all samples: decarburized layer, heat affected layer, and bulk metal. High machining efficiency can be obtained when the proper electrical parameters are selected, but whether high energy or the low energy is used, a coarse surface is always obtained. The variation of surface roughness and cutting rate with machining parameters is mathematically modeled by using the regression analysis method.
Keywords: nodular cast iron; regression analysis; WEDM